Antibiotic effectiveness on biofilm-producing Escherichia coli isolated from catheterized patients - Wani D Gunardi; Ade Dharmawan; Nicolas Layanto (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2022)
Biofilm is one of the factors that facilitate the occurrence of catheter-associated urinary tract infection (CAUTI). Escherichia coli is reported as one of the most dominant bacteria that have virulence factors including biofilm formation. Uropathogenic E. coli (UPEC) shows increasing resistance to several antibiotics. Examination of the antibiotic sensitivity on the biofilm-producing E. coli and its activity on biofilm formation are important for selecting high effectiveness antibiotics which is beneficial for the management of CAUTI patients. A total of 35 E. coli isolates were recultured in the medium of LB agar and blood agar. The isolates were evaluated the sensitivity based on their MIC value to several antibiotics. In addition, the antibiofilm activity of the antibiotics based on their MBIC value was also evaluated. The data obtained were analyzed both descriptively and analytically. Almost the E. coli isolates have good sensitivity to meropenem antibiotics, amoxicillin-clavulanic acid, and Fosfomycin. However, among the evaluated antibiotics, only fosfomycin that showed antibiofilm activity. The different in terms of the resistance phenotype between the urinary isolates and the catheter isolates was observed. However, there were no significantly differences in the MIC value (pMIC=0.522) and the MBIC value (pMBIC = 0.523). In conclusion, the alternatives of antibiotic therapy for the planktonic bacteria are amoxicillin-clavulanic acid and fosfomycin, while for the biofilm bacteria is fosfomycin. A biofilm screening examination on the catheter to improve the effectiveness of therapy management for CAUTI patients is recommended.